The role of humor-related traits and broad personality dimensions in irony use. (1st July 2017) - Bruntsch, Richard; Ruch, Willibald
Abstract: As humor has pervasively been postulated as a function of irony, humor-related traits such as the joy of laughing at others (i.e., katagelasticism) or trait seriousness can be assumed to predict who is more and who is less inclined to use verbal irony—even beyond the possible effect of broad personality dimensions. For the present study, N = 153 subjects made responses in two different irony use measures and completed personality questionnaires. As expected, irony use scores were higher among individuals who tend to break with social conventions, joyfully expose others' transgressions, or aggressively use ridicule (i.e., individuals scoring high in psychoticism, katagelasticism, or the aggressive humor style). Moreover, irony use was more prevalent among playful individuals who tend to entertain others by joyfully exposing themselves as the butt of jokes or engaging in as-if behaviors (i.e., low-serious individuals, scoring high in gelotophilia or the histrionic self-presentation style). Using a hierarchical regression analysis, it was found that over and above redundancy katagelasticism and—unexpectedly so—the self-defeating humor style predicted irony use beyond the influence of psychoticism. Accordingly, irony may also be seen a way to hide negative feelings behind humor and to avoid dealing constructively with problems. Highlights: Preexisting assumptions about the role of personality in irony use are tested. Humor is a pivotal aspect of irony for building hypotheses about relevant traits. A set of humor-related traits correlated substantially with measures of irony use. Humor-related traits predicted irony use beyond broad personality dimensions. Psychoticism, katagelasticism and self-defeating humor were unique predictors.